Neuroprotective Activity of Rasayana Formulation and Effect of Shigru Pallava Eye Drops on Intraocular Pressure as an Add-on Therapy Compared to the Standard of Care in Primary Open-Angle Glaucoma: Protocol for an Exploratory, Open-label, Two-arm Randomized Controlled Trial [version 1; peer review: 2 approved] - Manjusha Rajagopala; Deenadayal Devarajan (F1000Research)
Background Primary open-angle glaucoma (POAG) is a major cause of irreversible blindness worldwide, characterized by progressive optic neuropathy and loss of retinal ganglion cells (RGCs). Although lowering intraocular pressure (IOP) remains the mainstay of glaucoma management, many patients continue to experience vision loss, underscoring the need for adjunctive neuroprotective approaches. In Ayurveda, Rasayana therapies are believed to slow degenerative processes. One such intervention is a Rasayana Formulation (RF) comprising three oral preparations; Rasayana Churna (RC), Saptamrita Lauha (SL), and Yashada Bhasma (YB). Additionally, topical Arka (distilled extract) of Shigru Pallava (SP) has been used traditionally for glaucoma and may have an IOP-lowering effect. Methods This is an open-label, two-arm, parallel-group randomized controlled trial with a 2:3 (control: intervention) allocation ratio. A total of 50 previously or newly diagnosed POAG patients (IOP < 30 mmHg) are planned for enrollment. The control group receives the conventional standard of care alone, whereas the intervention group receives standard care plus RF (2.5 g, taken orally twice daily) and SP eye drops (1 drop, four times daily), administered for 90 days with a further 90-day follow-up. Primary outcomes include changes in optic nerve function measured by visual field indices (mean deviation (MD), pattern standard deviation (PSD), visual field index (VFI)) and retinal nerve fiber layer (RNFL) thickness, while secondary outcomes include IOP changes. Results Participant recruitment and data collection are ongoing. Final outcomes will be disseminated in peer-reviewed journals. Conclusions If shown to be effective, the combined RF and SP eye drops could enhance neuroprotection and further control IOP in POAG, thereby addressing a significant need in current glaucoma therapy. This trial may provide a foundation for larger-scale investigations into integrative treatments for glaucoma management. Trial Registration Clinical Trial Registry of India (CTRI) no. CTRI/2023/06/053681, dated 08.06.2023. Available from: https://trialsearch.who.int/Trial2.aspx?TrialID=CTRI/2023/06/053681 Protocol Version: 3.0, dated 05.01.2023